Language and society in Japan - Gottlieb, Nanette, 1948- (Contemporary Japanese society., 2005)
Nanette Gottlieb's book considers the role of language in Japanese society in relation to identity formation. It covers important questions such as multilingualism, language and nationalism, and literacy and reading habits. Building on the author's previous highly regarded work, it will be essential reading for students and scholars.